P162 Socio-economic status in patients with juvenile idiopathic arthritis in the United Kingdom. (23rd April 2022) - Tan, Yvonne; Costello, Ruth; Hyrich, Kimme; Humphreys, Jenny
Abstract: Background/Aims: Juvenile idiopathic arthritis (JIA) is a chronic inflammatory condition affecting children and young people (CYP) with onset <16 years, and may be associated with long-term joint damage and disability if treatment is delayed. CYP with JIA from low socio-economic status (SES) have been shown to have poorer performance in school activities and self-reported functional assessments compared to those from higher SES groups, however SES association with incidence of JIA has rarely been explored. Therefore, this study aimed to investigate the association between socio-economic status and incident JIA in England. Methods: CYP <16 years with a first JIA diagnostic code were identified in the Clinical Practice Research Datalink (CPRD) between the years 2000 and 2018, using a pre-defined codelist and were validated through linkage to Hospital Episode Statistics. Age- and gender-matched controls were identified at a ratio of 4:1. SES was defined using quintiles of indices of multiple deprivation (IMD). Descriptive analyses compared baseline characteristics (age, gender, age of first JIA code, IMD, region) in cases and controls. Logistic regression investigated the association between IMD quintiles in JIA cases compared to controls, adjusting for baseline characteristics, and linear regression analysed the association between age at first JIA code and IMD quintile. Results: There were 1649 cases and 4748 controls included in this study. Most cases (1048, 64%) were female with median (interquartile range (IQR)) age at first JIA code 8.49 (4.20-12.05) years. Amongst cases, males were older at first JIA code, median (IQR) 9.80 (6.09-12.68) years, compared to females 7.55 (3.45-11.70) years. In both cases and controls, the proportion of CYP was highest in the most deprived quintile (IMD 1), 375/1649 (22.7%) and 1108/4738 (23.4%) respectively, and proportions remained similar in the remaining quintiles. There was no association identified between IMD quintile and occurrence of JIA, the multivariable odds ratio (95% CI) comparing most and least deprived groups was 0.98 (0.83-1.17). However, amongst cases there was an association between older age at diagnosis and higher SES [ß(95%CI) 0.15 years (0.01-0.29)] such that CYP in the IMD 5 quintile (highest SES) were on average 8 months older at their first JIA code compared to CYP in IMD 1. Conclusion: This study found CYP from higher socio-economic groups appeared to be diagnosed at an older age than those from the least deprived backgrounds. Factors such as later presentation to healthcare after disease onset, delays in referrals to specialist care, delays in diagnosis by specialist care or differences in population demographics across IMD quantiles may all contribute to the older age of diagnosis in high SES group. Further research is required to explore these factors. Disclosure: Y. Tan: None. R. Costello: None. K. Hyrich: None. J. Humphreys: None.